Thermal decomposition of pyridoxine: an evolved gas analysis-ion attachment mass spectrometry study - Juhász, Márta; Takahashi, Seiji; Kitahara, Yuki; Fujii, Toshihiro (Rapid Communications in Mass Spectrometry, 2012)
RATIONALE Pyridoxine is an important vitamer in food and pharmaceutical products. Heat treatments applied during preparation or storage of the products cause the decomposition of pyridoxine. Identification and understanding of the degradation products of pyridoxine and studying its decomposition kinetics are essential in the preparation and preservation of pyridoxine‐containing foods and pharmaceuticals. METHODS Real‐time, non‐isothermal decomposition of pyridoxine was studied using evolved gas analysis‐Li+ ion attachment mass spectrometry (EGA‐Li+IAMS). Arrhenius parameters for the thermal decomposition of pyridoxine were obtained via the total ion monitoring (TIM) curve. RESULTS Most of the pyridoxine evaporated in molecular form, but the formation of pyridoxal and o‐quinone methide, both biologically important species, was also observed from the solid‐phase degradation of pyridoxine. The observation of o‐quinone methide, a species possessing anticancer activity, was particularly noteworthy due to its chemical instability. The activation energy (Ea) for pyridoxine decomposition determined by EGA‐IAMS was found to be 20.0 kcal mol–1, and the pre‐exponential factor (A) was 5.7 × 109 min–1. CONCLUSIONS The calculated kinetic parameters are important for predicting the thermal stability of pyridoxine vitamer. The estimated lifetime (t90%,25°C) of 1.7 × 10–2 years in nitrogen was also obtained from the EGA‐IAMS experiment. Copyright © 2012 John Wiley & Sons, Ltd.